Iowa Birdline update, August 1, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Emails for the Iowa Birdline update for August 1-4, 1994. Highlights of the updates include sightings of Black-headed Gulls and a juvenile Laughing Gull as well as the continued presence of a Pacific Loon. Also of note were the observations of numerous shorebirds, all nine regular species of Herons, 11 young Barn Owls, 100 Great Egrets, and 250 American White Pelicans. Epson - sheet feed/flatbed